Perancangan Dimensional Model dan Aplikasi Dashboard Bagi Unit Karir Perguruan Tinggi - Rudy Rudy (Bina Nusantara University, 2013)
College career unit is equipped with a web-based application that can be used by job seekers and employers. The application results in operational reports in accordance with the existing transactions. Transaction data is stored in an OLTP (online transaction processing) and can be used for analysis. For data analysis needs a unit career of a college can use dashboard application that displays information in graphical forms which are easily understood. As the data sources used dimensional dashboard application model introduced by Kimball that is data mart. The result achieved is a dashboard application that can be used by thecollege management to get quick information and detail that can be viewed from a variety of dimensions. Dimensional models and dashboard applications developed are related to the calculation of job seeker registration, positions offered, labor required by employers and employer registration.